2014
DOI: 10.1182/blood-2013-11-540534
|View full text |Cite
|
Sign up to set email alerts
|

A von Willebrand factor fragment containing the D′D3 domains is sufficient to stabilize coagulation factor VIII in mice

Abstract: • The D9D3 domains of VWF are sufficient to stabilize FVIII in vivo.• The prolongation of VWF D9D3 survival in vivo by Fc fusion elevates FVIII levels in the setting of VWF but not FVIII deficiency.Plasma factor VIII (FVIII) and von Willebrand factor (VWF) circulate together as a complex. We identify VWF fragments sufficient for FVIII stabilization in vivo and show that hepatic expression of the VWF D9D3 domains (S764-P1247), either as a monomer or a dimer, is sufficient to raise FVIII levels in Vwf 2/2 mice f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 55 publications
1
64
0
Order By: Relevance
“…Several phase 1/2 studies are underway, and preliminary analyses have shown that ricolinostat has clinical activity in patients with RRMM when combined with bortezomib and low-dose dexamethasone [70], lenalidomide and dexamethasone [71], and pomalidomide and dexamethasone [72]. Additionally, its selective HDAC6 inhibition is expected to result in increased tolerability.…”
Section: Treatment Of Rrmm In Europe: the Current Therapeutic Landscapementioning
confidence: 99%
“…Several phase 1/2 studies are underway, and preliminary analyses have shown that ricolinostat has clinical activity in patients with RRMM when combined with bortezomib and low-dose dexamethasone [70], lenalidomide and dexamethasone [71], and pomalidomide and dexamethasone [72]. Additionally, its selective HDAC6 inhibition is expected to result in increased tolerability.…”
Section: Treatment Of Rrmm In Europe: the Current Therapeutic Landscapementioning
confidence: 99%
“…6 We and others have previously reported that VWF fragments are sufficient to bind FVIII and that propeptide processing of these VWF fragments enhances the affinity for FVIII. [7][8][9] Several of these VWF fragments were also sufficient to elevate FVIII levels in VWF-deficient mice. 7 To further explore the association between VWF and FVIII, we used single-particle negative-stain electron microscopy (EM) to characterize the architecture of dimeric VWF D9D3 domains ([D9D3] 2 ) alone and in complex with FVIII.…”
Section: Introductionmentioning
confidence: 98%
“…5,6 Consistent with these findings, recombinant D9D3 domains have been shown to be sufficient to elevate levels of endogenous FVIII in VWF-deficient mice. 7 The reciprocal binding site for VWF on FVIII was initially localized broadly to its light chain. 8 Subsequent studies demonstrated that the a3 acidic peptide region (E1649-R1689) 9 and a restricted fragment thereof (K1673-R1689), 10 as well as sulfation on residue Y1680 within this region, are important for VWF binding.…”
Section: Introductionmentioning
confidence: 99%